The use of podcasts in the speaking skill development of English as a foreign language - Guerrero Guevara, Fabricio Daniel (2023)
The present investigation was conducted to determine the effectiveness of using podcasts in the development of English Speaking Skill in the students from sixth level of the Language Department at Pontificia Universidad Católica Sede Ambato. Nowadays, English teachers incorporate a variety of teaching materials that support their classes by generating a scenario where students are able to experience the English language in a more excellent form. However, circumstances as the limited time in the class and the materials used during it do not allow students to expand their exposure to the English language, therefore the development of English speaking skill are reduced. This investigation applied a quasi-experimental method that managed a control group and an experimental group. Each of these groups consisted of fifteen students from the sixth level of English. The implementation of a pretest and a posttest contributed as a data collection technique in order to examine the results. In addition, a survey was conducted to the students in the interest of their perception towards the use of podcasts. This investigation aimed to determine the impact of using podcasts on the English speaking skill development by analyzing its influence and identifying the elements that contribute to this skill. The examined results concluded that students upgraded their level, from a basic to an intermediate level, demonstrating the effectiveness of using podcast with an emphasis on the listening skill to the development of the English Speaking skill.